2022
DOI: 10.1136/bmjhci-2021-100493
|View full text |Cite
|
Sign up to set email alerts
|

Connecting artificial intelligence and primary care challenges: findings from a multi stakeholder collaborative consultation

Abstract: Despite widespread advancements in and envisioned uses for artificial intelligence (AI), few examples of successfully implemented AI innovations exist in primary care (PC) settings.ObjectivesTo identify priority areas for AI and PC in Ontario, Canada.MethodsA collaborative consultation event engaged multiple stakeholders in a nominal group technique process to generate, discuss and rank ideas for how AI can support Ontario PC.ResultsThe consultation process produced nine ranked priorities: (1) preventative car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…This enabled us to create and refine a tool which is useful to all groups, for a range of purposes specific to each. While other studies report that an artificial intelligence tool generated concerns, 23 our stakeholders reported no concerns but were unanimously supportive and enthusiastic, citing visualisation functions as its greatest strength. Stakeholders had almost no criticisms of the tool, instead recognising its potential and desiring additional features.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This enabled us to create and refine a tool which is useful to all groups, for a range of purposes specific to each. While other studies report that an artificial intelligence tool generated concerns, 23 our stakeholders reported no concerns but were unanimously supportive and enthusiastic, citing visualisation functions as its greatest strength. Stakeholders had almost no criticisms of the tool, instead recognising its potential and desiring additional features.…”
Section: Discussionmentioning
confidence: 58%
“…PPPI on health data typically focuses on artificial intelligence, 23 patient portals 24 and decision-making tools 25 and recommend problem solving by understanding the relationship between data capabilities and the role of patients and the public. 23–26 Few involvement activities have focused specifically on providing public-facing data visualisations that are also useful to researchers, data professionals and clinicians. Our work contributes to the literature by consulting with all relevant stakeholder groups and synthesising their contributions.…”
Section: Discussionmentioning
confidence: 99%
“…7 Before widespread implementation of AI tools, we need to better understand frontline staff and providers' perceptions on using AI to help deliver optimal primary care. A recent scoping review on perceptions about increasing use of AI in health care identified only a few studies within primary care, 12 where some focused on opinions of research and policy stakeholders 13,14 and others used a survey design. 15,16 We conducted this study to inform an agenda for AI research within a province-wide primary care Learning Health Organization in Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports the findings from one of a series of studies designed to explore these issues [22]. This qualitative study explored the uses of AI in primary health care.…”
Section: Introductionmentioning
confidence: 99%